2008
DOI: 10.1007/s10741-008-9108-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of vasopressin antagonists

Abstract: Congestive heart failure (CHF) is characterized by fluid and water retention, which frequently is a therapeutic challenge. Most conventional diuretics act primarily as saluretics, i.e. they inhibit renal tubular electrolyte reabsorption, which due to osmotic pressure promotes excretion of isotonic fluid. Arginine vasopressin (AVP) via the V(1A) receptor vasoconstricts and via the V(2) receptor promotes water reabsorption in the renal collecting duct by inserting aquaporin-2 water channels into the luminal memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Specific V2 receptor antagonists, so-called "aquaretic agents," block the action of AVP on collecting duct cells and are being developed for the treatment of hypotonic hyponatremia in water-retaining disorders such as the syndrome of inappropriate antidiuretic hormone secretion, liver cirrhosis, and congestive heart failure (4,6,29,51). OPC-31260, a nonpeptide V2 receptor antagonist, administered to animals orthologous to human PKD, including Pkd2 WS25/Ϫ mouse (ADPKD), PCK rat (ARPKD), and pcy mouse (nephronophthisis type 3), reduced renal cAMP and dramatically halted disease progression measured by reductions in kidney volume, cystic area, number of mitotic cells, and blood urea nitrogen (12,35,42).…”
mentioning
confidence: 99%
“…Specific V2 receptor antagonists, so-called "aquaretic agents," block the action of AVP on collecting duct cells and are being developed for the treatment of hypotonic hyponatremia in water-retaining disorders such as the syndrome of inappropriate antidiuretic hormone secretion, liver cirrhosis, and congestive heart failure (4,6,29,51). OPC-31260, a nonpeptide V2 receptor antagonist, administered to animals orthologous to human PKD, including Pkd2 WS25/Ϫ mouse (ADPKD), PCK rat (ARPKD), and pcy mouse (nephronophthisis type 3), reduced renal cAMP and dramatically halted disease progression measured by reductions in kidney volume, cystic area, number of mitotic cells, and blood urea nitrogen (12,35,42).…”
mentioning
confidence: 99%
“…However, we are not aware of any evidence demonstrating a protective effect and positive prognosis associated with furosemide administration at the time of acute MI. Tolvaptan was developed as a new diuretic drug that exerts an aquaretic effect by blocking the V 2 R at the renal collecting duct, thereby inhibiting water reabsorption (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown (7 -9). A non-peptide AVP V 2 R antagonist, tolvaptan (6,10), does not affect the RAAS. The large, multi-centre trial Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study with Tolvaptan (EVEREST) revealed that chronic tolvaptan administration was safe and induced aquaresis, which was evidenced by body weight reduction during the initial hospitalization period following acute decompensated HF.…”
Section: Introductionmentioning
confidence: 94%
“…Satavaptan is an AVP receptor antagonist with enhanced affinity to V 2 R compared to V 1a R [61,62]. Thus, satavaptan inhibits AVP binding to the human V 2 R with a K i of 4.1 ± 0.8 nM;…”
Section: Satavaptanmentioning
confidence: 99%
“…However, the application Maximal plasma concentrations of the substance were observed 3h after administration; mean plasma concentration increased with dosage and duration of drug application and stabilized on day 5. The major route of excretion was via feces [62]. Satavaptan is available as an oral preparation at 5-50 mg dosages; the aquaretic effect following the drug administration persists up to 12 hours [64].…”
Section: Satavaptanmentioning
confidence: 99%